Different epitopes of Ralstonia solanacearum effector RipAW are recognized by two Nicotiana species and trigger immune responses. (31st October 2021) - Niu, Yang; Fu, Shouyang; Chen, Gong; Wang, Huijuan; Wang, Yisa; Hu, JinXue; Jin, Xin; Zhang, Mancang; Lu, Mingxia; He, Yizhe; Wang, Dongdong; Chen, Yue; et al.
Abstract: Diverse pathogen effectors convergently target conserved components in plant immunity guarded by intracellular nucleotide‐binding domain leucine‐rich repeat receptors (NLRs) and activate effector‐triggered immunity (ETI), often causing cell death. Little is known of the differences underlying ETI in different plants triggered by the same effector. In this study, we demonstrated that effector RipAW triggers ETI on Nicotiana benthamiana and Nicotiana tabacum . Both the first 107 amino acids (N1‐107 ) and RipAW E3‐ligase activity are required but not sufficient for triggering ETI on N .  benthamian a. However, on N .  tabacum, the N1‐107 fragment is essential and sufficient for inducing cell death. The first 60 amino acids of the protein are not essential for RipAW‐triggered cell death on either N .  benthamiana or N . tabacum . Furthermore, simultaneous mutation of both R75 and R78 disrupts RipAW‐triggered ETI on N .  tabacum, but not on N .  benthamiana . In addition, N .  tabacum recognizes more RipAW orthologs than N .  benthamiana . These data showcase the commonalities and specificities of RipAW‐activated ETI in two evolutionally related species, suggesting Nicotiana species have acquired different abilities to perceive RipAW and activate plant defences during plant–pathogen co‐evolution. Abstract : Nicotiana species show differential recognition systems for the same pathogen effector.